2012
DOI: 10.1590/s0103-50532012005000068
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Chirita longgangensis var. hongyao with inhibitory activity against porcine respiratory and reproductive syndrome virus

Abstract: Dois novos quinenóides chiritalona A and B, e uma nova neolignina 7'E-4,9-dihidroxi-3,3',5'-trimethoxi-8,4'-oxineolign-7'-en-9'-al, além dos conhecidos (-)-8-hidroxi-α-dunniona, digiferruginol, 2,5-dimetoxi-1,4-benzoquinona e hederagenina, foram isolados do caule de Chirita longgangensis var. hongyao. As estruturas dos novos compostos foram elucidadas por análise detalhada de dados obtidos pela técnicas de NMR (ressonância magnética nuclear) e MS (espectrometria de massas), e a configuração absoluta de chirita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The spectroscopic data suggested that 2 belong to the urs-12-en-28-oic acid series. This suggestion confirmed by 1 The α configuration of hydroxy group at C-3 was identified by the chemical shift and multiplicity of hydroxy-methine proton. Consequently, 2 was determined as 3 ,24-dihydroxy-urs-12-en-28-oic acid by comparison with spectroscopic data in literature.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The spectroscopic data suggested that 2 belong to the urs-12-en-28-oic acid series. This suggestion confirmed by 1 The α configuration of hydroxy group at C-3 was identified by the chemical shift and multiplicity of hydroxy-methine proton. Consequently, 2 was determined as 3 ,24-dihydroxy-urs-12-en-28-oic acid by comparison with spectroscopic data in literature.…”
Section: Resultsmentioning
confidence: 55%
“…Chirita is the oldest genus of the Gesneriaceae family, distributed in Malaysia, Southeast Asia and south of China. Some Chirita species are used in folk medicine as poultice, hemostasis agents or for treatment of hypertension, .... [1] There are about 20 Chirita species in Vietnam. [2] Until now, there have been only a few studies on chemical and biological activities of the Chirita species, but they revealed interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary data: 1 H and 13 C NMR spectra and HR-MS spectra of all isolated compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), 2D NMR spectra of the new compounds 1 and 2, NMR data of the acetylated derivative 2a.…”
Section: Methodsmentioning
confidence: 99%
“…Based on molecular phylogenetic investigations Chirita was recently recognized as an artificial, polyphyletic genus and therefore reorganized transferring parts of the genus to Primulina [2]. In the folk medicine, some Chirita species are used for the treatment of bone fractures, wounds, pains, arthritis and anemia [3]. Previous phytochemical studies on other Chirita species revealed mainly phenylethanoid glycosides, flavonoids and quinines [4][5][6][7][8].…”
mentioning
confidence: 99%